2010
DOI: 10.1007/s10483-010-1371-6
|View full text |Cite
|
Sign up to set email alerts
|

Flow of a biomagnetic viscoelastic fluid: application to estimation of blood flow in arteries during electromagnetic hyperthermia, a therapeutic procedure for cancer treatment

Abstract: The paper deals with the theoretical investigation of a fundamental problem of biomagnetic fluid flow through a porous medium subject to a magnetic field by using the principles of biomagnetic fluid dynamics (BFD). The study pertains to a situation where magnetization of the fluid varies with temperature. The fluid is considered to be non-Newtonian, whose flow is governed by the equation of a second-grade viscoelastic fluid. The walls of the channel are assumed to be stretchable, where the surface velocity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 35 publications
0
30
0
1
Order By: Relevance
“…[21]) to linearize the discretized equation. The numerical procedure have been presented by Misra and Shit [22] and Misra et al [23][24] in detail. The essential feature of this technique is that it is based on an iterative procedure with good stability and simple and tri-diagonal manipulation.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…[21]) to linearize the discretized equation. The numerical procedure have been presented by Misra and Shit [22] and Misra et al [23][24] in detail. The essential feature of this technique is that it is based on an iterative procedure with good stability and simple and tri-diagonal manipulation.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The effect is attained by overheating the cancerous tissues (Szasz, 2007) by means of electromagnetic radiation. Misra et al (2010) reported theoretical estimates of blood flow in arteries during the therapeutic procedure of electromagnetic hyperthermia used for treatment of cancer. A few important discussions are also available in that paper.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…To solve this tri-diagonal system of equations, we have used the ''Tri-diagonal matrix algorithm'', usually referred as ''Thomas algorithm'' (cf. [47][48][49]). It may be mentioned here that instead of this, one could use Gauss elimination method.…”
Section: Heat Mass Transfer (2013) 49:617-628 621mentioning
confidence: 99%
“…Szasz [11]) by means of electromagnetic radiation. Misra et al [12] reported theoretical estimates of blood flow in arteries during the therapeutic procedure of electromagnetic hyperthermia used for cancer treatment. Some relevant useful discussions are also available in that paper.…”
Section: Introductionmentioning
confidence: 99%